A possibilidade da fazenda pública requerer a falência dos empresários, das sociedades empresárias e das empresas paraestatais - MENDES, Dângelo Wesley Oliveira (2023)
This paper analyzes a theme related to Constitutional, Administrative, Procedural and Bankruptcy Law. In view of this, despite the fact that there is no doubt about the application of the Law on Judicial Recovery and Bankruptcy (Law No. 11,101 / 2005) to the private sector, the same does not occur with respect to the applicability or not of the said Law to public entities that exploit activity economical. Notwithstanding these discussions, controversy persists regarding the legitimate interest of the Treasury to file for bankruptcy of companies, public or private, indebted to the State, to the detriment of other legitimate means available to the Public Treasury to collect its credits. However, significant changes in the law and jurisprudence in 2020 allude to a path with new interpretations to be discussed by the Courts, which are projected within the scope of this Work. Thus, for the development and analysis of institutes of the different branches of law related to this theme, it uses research carried out on the Internet, in published articles, in consultation with jurisprudence, as well as with the relevant legal and doctrinal framework. In the end, the study examines the compatibility of such institutes with the principles related to the Brazilian legal system.